2D.06: IN HYPERTENSIVE PATIENTS WITH CHEST PAIN AND NORMAL RESTING ECG THE LOW-COST EXERCISE HIGH-FREQUENCY QRS-ANALYSIS IS COMPARABLE TO THE EXERCISE ECHO. (June 2015) - Conti, A.; Bianchi, S.; Trausi, F.; Grifoni, C.; Angeli, E.; Paolini, D.; Catarzi, S.; Perrotta, M.E.; Covelli, A.; Renzi, N.; Bertolini, P.; Mazzucchelli, M.
Abstract : Objective: The novel exercise computer-assisted high-frequency QRS-analysis (ex-HF/QRS) has demonstrated improved sensitivity and specificity over the conventional ST/ECG-segment analysis (ex-ST/ECG) in the detection of myocardial ischemia. The aim of the present study was to compare the diagnostic value of the validated exercise-Echocardiography (ex-Echo), needing skilled cardiologist, with the novel low-cost ex-HF/QRS, including the conventional ST-segment analysis. Design and method: A prospective cohort study was conducted in the Emergency Department of a tertiary care teaching Hospital, and validated by the Propensity Score Model. Patients with chest pain (CP), normal resting ECGs, troponins, echocardiography and "intermediate-risk" for adverse coronary events underwent the ex-HF/QRS and ex-Echo. An ST-segment depression >/=2 mV or >/=1 mV when associated with CP were considered as index of ischemia, as a decrease >/=50% in HF/QRS intensity or new wall motion abnormalities on ex-Echo. Exclusion criteria were QRS duration >/=120 milliseconds, poor echo-acoustic window and inability to exercise. The endpoint was the composite of coronary stenoses >50% at angiography or acute coronary syndrome, revascularization and cardiovascular death on the six-month follow-up. Results: In 270 patients enrolled, the ex-HF/QRS and ex-Echo showed comparable predictive values with p = NS for all comparisons as follows: negative predictive value 97% vs 96%, respectively; sensitivity 63% versus 65%, respectively; specificity 64% versus 83%, respectively. The areas on Receiver Operator Characteristics analysis were comparable (ex-HF/QRS: 0.65, 95% CI 0.51–0.77 vs ex-Echo: 0.66, CI 0.56–0.86; C statistic p = NS). On multivariate analysis, both ex-HF/QRS and ex-Echo were predictors of the endpoint. Conclusions: In "intermediate-risk" CP patients, the novel ex-HF/QRS was a valuable diagnostic tool in the crowed Emergency Departments. The test might be proposed to avoid additional costly imaging also because it did not require specialized personnel. However, additional study are needed before it can be recommended as a replacement for current techniques.